Improving Classical Playfair Cipher Security Using Genetic Algorithm-Based Key Optimization - Elvis Pawan; Friden Elefri Neno; Yuliana Yuliana; Putri Dwi Febriana; Damianus Da Awendu (PT. GWEX NET PUBLISHER, 2026)
Even though the need for data security is growing, the standard Playfair Cipher algorithm can still be broken by frequency analysis. This is why this study was done. Ciphertext patterns that are easy to guess are a big problem because they make things less safe. This is especially true for the Playfair Cipher, which can be broken into by frequency analysis if it isn't properly protected. To make things safer, it is important to use stronger encryption methods and update the key management process on a regular basis. As part of designing the algorithm, building the system, and testing how well the cryptosystem works, you need to change the structure of the matrix and shuffle the keys on the fly. The test showed that the time it took to encrypt went up from 12.0 milliseconds to 14.2 milliseconds (+2.2 milliseconds or +18.33%), but the accuracy of the decryption stayed at 100%. The random index value also rose from 0.03636 to 0.06061. This means that the ciphertext is getting more random. The results show that making changes to the Playfair Cipher can make it a lot safer while still keeping it fast enough